1974
DOI: 10.1017/s0022172400023445
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of infection with Tana and Yaba pox viruses among several species of monkey

Abstract: SUMMARYSera from cynomolgus monkeys from Malaysia, from Indian rhesus monkeys, from various species of monkeys from Africa and from South America have been examined for neutralizing antibody to Tanapox and Yaba viruses. No antibody was found to either virus in the sera of rhesus monkeys or South American monkeys. A certain proportion of sera from cynomolgus monkeys and various species of African monkey showed antibody to one or other of the viruses, but few of the positive sera showed antibody to both. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The unique circumstances responsible for the initial outbreak of YLDV infection in macaques are unrecognized. Serologic surveys indicate natural infection of African but not New World primates (Downie, 1972;Downie and Espana, 1974).…”
Section: Epizootiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The unique circumstances responsible for the initial outbreak of YLDV infection in macaques are unrecognized. Serologic surveys indicate natural infection of African but not New World primates (Downie, 1972;Downie and Espana, 1974).…”
Section: Epizootiologymentioning
confidence: 99%
“…Serologic surveys indicate natural infection of African but not New World primates (Downie, 1972;Downie and Espana, 1974).…”
Section: Epizootiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Some species (Indian Macaca mulatta) had no antibody, and the average incidence in those species with some positive individuMs was 14 per cent (18). The percentage of monkeys with neutralizing antibodies to Tanapox virus varies from 2 per cent (Kenyan Erythrocebus patas) to 25 per cent (Liberian Cercopithecus and Colobus).…”
Section: Definin 9 Hosts and Reservoirsmentioning
confidence: 99%
“…These studies indicated that Tanapox infection had occurred in various species of monkey in Africa and in macacus monkeys in Malaysia. Tanapox antibodies were absent from the sera of rhesus monkeys from India and from various species of monkey in the new world (Downie, 1974). In 1971 the examination of sera from natives living in the flood plain area by the Tana river suggested that Tanapox infection had continued to occur in the population of that area since the outbreak in 1962 (Manson-Bahr & Downie, 1973).…”
Section: Introductionmentioning
confidence: 99%